Genetics, genomics, and diet interactions in obesity in the Latin American environment - Guevara-Ramírez, Patricia; Cadena-Ullauri, Santiago; Ruiz-Pozo, Viviana A.; Tamayo-Trujillo, Rafael; Paz-Cruz, Elius; Simancas-Racines, Daniel; Zambrano, Ana Karina (Frontiers in Nutrition, 2022)
Obesity is a chronic disease characterized by abnormal or excessive fat accumulation that could impact an individual’s health; moreover, the World Health Organization has declared obesity a global epidemic since 1997. In Latin America, in 2016, reports indicated that 24.2% of the adult population was obese. Genes could define susceptibility to a condition or disease, and the environmental factor or specific behaviors like dietary intake or physical activity could determine the development of that condition or disease such as obesity; hence, it is vital to understand the relationship between genes and disease. Indeed, nutrigenetics studies genetic variations and their effect on dietary response; while nutrigenomics study the role of nutrients in gene expression. The present review represents a compendium of genes and their SNPs associated with obesity, including the risk allele frequencies in the Latin American population. Additionally, a bibliographical selection of several studies has been included; these studies examined the impact that diet has on the expression of numerous genes involved in obesity-associated metabolic pathways.